Two‐stage additional evidence support association of common variants in the HDAC3 with the increasing risk of schizophrenia susceptibility. Issue 8 (30th August 2016) - Jia, Xiaodi; Zhang, Tianxiao; Li, Lu; Fu, Dongke; Lin, Huali; Chen, Gang; Liu, Xinshe; Guan, Fanglin
Abstract : Schizophrenia (SCZ) is a complex neuropsychiatric disorder with high heritability. Abnormal gene methylation was found to play a key role in the development of SCZ, suggesting that histone deacetylases (HDACs) may increase the expression of several key genes in the brain. However, recent studies evaluating the association between SCZ and genetic polymorphisms in histone deacetylase 3 (encoded by HDAC3 ) have shown conflicting results. In this study, we designed a two‐stage case‐control study to investigate the association of the HDAC3 with SCZ. Fourteen tag single nucleotide polymorphisms (SNPs) entirely covering the region of HDAC3 were analyzed in the testing group of 1, 421 patients and 2, 823 healthy controls, and the SNP rs14251 was found to be significant (and rs2530223 to be nominally significant). The significant result of rs14251 was successfully replicated in the validation group consisting of 896 cases and 1, 815 healthy controls ( P = 0.009276, OR = 1.219), and also confirmed by haplotype based analyses (rs976552‐rs14251, global P < 0.001). To sum up, our results provide additional evidence that HDAC3 confers the increasing risk of SCZ susceptibility in Han Chinese individuals, suggesting this gene as a potential genetic modifier for SCZ development. © 2016 Wiley Periodicals, Inc.